Measurement of the Cosmic Microwave Background Polarization with the BICEP Telescope at the South Pole - Takahashi, Yuki David (eScholarship, University of California, 2010)
The question of how exactly the universe began is the motivation for this work. Based on the discoveries of the cosmic expansion and of the cosmic microwave background (CMB) radiation, humans have learned of the Big Bang origin of the universe. However, what exactly happened in the first moments of the Big Bang? A scenario of initial exponential expansion called "inflation" was proposed in the 1980s, explaining several important mysteries about the universe. Inflation would have generated gravitational waves that would have left a unique imprint in the polarization of the CMB. To search for this evidence for inflation, a team gathered in 2002 to design a telescope experiment called BICEP. Sited at the South Pole, BICEP was a novel 25-cm aperture refractor with 49 pairs of polarization-sensitive bolometers. We completed 3 years of successful observations from February 2006 to December 2008. To constrain the amplitude of polarization resulting from inflation, expected to be at least 7 orders of magnitude fainter than the 3 K CMB intensity, precise control of systematic effects is essential. A crucial challenge is preventing systematic errors from introducing false polarization anisotropy signal at the level corresponding to ~0.1 μK in amplitude. One main focus of this thesis is the characterization of systematic effects for BICEP. We developed a simulation framework for propagating instrumental systematic effects to the final polarization results. Based on these simulations, we established benchmarks for the characterization of critical instrumental properties including bolometer relative gains, beam mismatch, polarization orientation, telescope pointing, sidelobes, thermal stability, and timestream noise model. Guided by these benchmarks, we carefully measured these properties and have shown that we have characterized the instrument adequately to ensure that systematic errors do not limit BICEP's current cosmology results. We have analyzed the first 2 years of data, lowering the upper limits on the gravitational-wave induced polarization by an order of magnitude over all previous experiments. The systematic error analysis has identified what future refinements are likely necessary to probe CMB polarization down to levels corresponding to inflationary energy scales below 2 × 1016 GeV.